Role of lifestyle behaviours in the ethnic pattern of poor health outcomes in Leicester, England: analysis of a survey data set. (May 2019) - Chattopadhyay, Kaushik; Akagwire, U.; Biswas, M.; Moore, R.; Rajania, G.; Lewis, S.
Abstract: Objectives: Mediation analyses were conducted to explore the contribution of lifestyle behaviours in the ethnic pattern of poor health outcomes in Leicester, England. Study design: Cross-sectional study. Methods: The study used data on 1959 participants from the Leicester Health and Well-being Survey (2015). Lifestyle behaviours were physical activity, diet, smoking and alcohol drinking. Poor health outcomes were the presence of long-term illness and poor self-reported health. Results: Poor health outcomes were less common in Black and Minority Ethnic groups (BMEs) than Whites. Smoking was less common in BMEs than Whites. Poor health outcomes were more common in ex-smokers and current smokers than never smokers. Health outcomes were associated with smoking even after adjusting for ethnicity. The association of ethnicity and health outcomes reduced after adjusting for smoking, suggesting that the effect was mediated by smoking. Conclusions: In Leicester, Whites had poorer health outcomes than BMEs, which were not mediated by physical activity, diet and alcohol drinking but were mediated by smoking. Highlights: Mediation analyses were conducted using data from the Leicester Health and Well-being Survey (2015), England. In Leicester, Whites had poorer health outcomes than Black and Minority Ethnic groups. In Leicester, poorer health outcomes were not mediated by physical activity, diet and alcohol drinking but by smoking.